Design and research progress of nano materials in cathode catalysts of microbial fuel cells: A review. (12th May 2022) - Chen, Junfeng; Yang, Jiaqi; Wang, Renjun; Yang, Yuewei; Liu, Yanyan
Abstract: With the advantages of clean, efficient and energy-saving, microbial fuel cells (MFCs) were characterized with perfect significance in the field of degrading environmental pollutants and generating electricity meanwhile. The cathode materials affected the activity of oxygen reduction reaction (ORR), and affected the power generation performance for MFCs. There were many kinds of nano materials played an important role in the field of cathode catalysis. The advantages of metal and non-metal composites were easy to obtain and low cost; layered double hydroxide (LDH) was easy to control and compound, and could be fully realized functionalization; metal organic frameworks (MOFs) were widely used since their porosity, high specific surface area and high activity; covalent organic frameworks (COFs) were low density and easy to be modified, so as to modify and realize functionalization; MXene was an excellent two-dimensional material, which could provide more channels for the movement of ions. The nano materials formed by the composite of various materials combined the advantages of various materials and played key role in improving ORR performance of MFCs. Graphical abstract: Image 1 Highlights: The design and synthesis of typical nano materials were analyzed. Research progress of nano materials in cathode catalysts of MFC was reviewed. The application of nano materials in cathode catalysis of MFC was discussed.